Method for preparing metal organic framework film layer with self-repairing performance through electro-deposition method

The metal organic frame film layer coated with polyphenol compound tannin acid was prepared on the surface of the aluminum alloy by electrodeposition method, which solved the complex process and pollution problems in the prior art, and achieved efficient and environmentally friendly corrosion protection.

CN119465333AActive Publication Date: 2025-02-18GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411553713.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-03
Publication Date
2025-02-18
Estimated Expiration
2044-11-03

AI Technical Summary

Technical Problem

The prior art When preparing metal organic frame film layers, the process is complicated, it is prone to contamination, and the bonding force is poor, which affects the corrosion resistance.

Method used

The process is simplified and waste liquid is reduced by using electrodeposition method to prepare a metal organic frame film layer coated with polyphenol compound tanninic acid on the surface of aluminum alloy. emission.

Benefits of technology

It realizes a self-repair corrosion-resistant film layer with simple process, short time and good bonding force, significantly improves the corrosion resistance of the aluminum alloy surface and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465333A_ABST
    Figure CN119465333A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a metal organic framework film layer with self-repairing performance by an electro-deposition method, which comprises the following steps of: pressurizing and oxidizing aluminum alloy serving as an anode and an aluminum foil serving as a cathode in a tannic acid solution to form an anodic oxide film on the surface of the aluminum alloy to obtain an anodized aluminum alloy; adding N, N-dimethylformamide, a metal source and trimesic acid into the reacted tannic acid solution, and uniformly mixing to obtain a film layer preparation solution; and the aluminum alloy subjected to anodic oxidation serves as a cathode, graphite serves as an anode, electro-deposition is carried out in the film layer preparation liquid, and the self-repairing film layer is formed on the aluminum alloy. Tannic acid is used as an acid solution of the anodic oxidation solution, so that a layer of anodic oxidation film can be prepared on the metal surface, and the tannic acid can be continuously used as a raw material for subsequently preparing a metal-MOF self-repairing film layer; the use of waste acid is reduced, and meanwhile, the preparation process is simplified; the electrochemical performance and the corrosion resistance of the film layer are improved, and the film layer has good self-repairing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of corrosion-resistant intelligent film layers of metal materials, and in particular to a method for preparing a metal organic framework corrosion-resistant self-repairing film layer containing a polyphenol compound tannic acid on an aluminum alloy surface. Background Art

[0002] Aluminum alloys are widely used in transportation vehicles, machinery and equipment, and buildings due to their low density, high strength, and convenient processing. Many machines and equipment are used in marine tidal environments. Although aluminum alloys will produce dense oxide films in air environments, when aluminum alloys are exposed to an environment with corrosive media, the oxide films will become uneven, causing galvanic corrosion, pitting, stress corrosion cracking, and other problems. These situations will shorten the service life of the metal and even damage the device, burying safety hazards. In response to these problems, researchers have used many processing technologies, among which the metal organic framework film layer can slow down the reaction between the cathode and the anode, increase the invasion path of the corrosive medium, and thus block its corrosion process on the metal. After contacting the metal, polyphenol compounds can form a film on the metal surface. This film is a metal complex with anti-corrosion ability. The polyphenol compound is coated in a metal organic framework with adjustable pore size, so that an active and passive anti-corrosion mode can be achieved, and the corrosion inhibitor can still be released after the film layer is destroyed to provide secondary protection for the metal.

[0003] There are many methods for preparing MOF film-coated corrosion inhibitors, but most methods require the preparation of MOF-coated corrosion inhibitor powders first, then adding them to a certain coating, and finally applying them on the metal surface by coating. This method is time-consuming and labor-intensive, and is prone to problems such as poor bonding strength. In patent CN116815268A, a mixed solution of phosphoric acid and oxalic acid is first used as an electrolyte for anodization to an aluminum alloy, and then an electrodeposition method is used to further prepare a MOF film layer on the surface of the aluminum alloy, which can reduce the reaction time to a certain extent and improve the bonding strength. However, in its preparation process, the remaining mixed solution after the anodization is completed becomes waste liquid, and an electrolyte solution needs to be prepared separately when preparing MOF in the subsequent preparation, which makes the process complicated and easily produces unnecessary pollution sources. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a metal-MOF organic framework film layer with self-repairing properties. The self-repairing corrosion-resistant film layer of MOF coated with corrosion inhibitor is directly prepared on the metal surface by electrodeposition, which has the advantages of simple process, short time and good bonding force. The polyphenol compound tannic acid is directly prepared into an anodic oxidation electrolyte for preparing an anodic oxidation layer; at the same time, the solution can still be used as a part of the solution in the subsequent steps, and continue to participate in the experiment after the anodization is completed to provide a corrosion inhibitor, and then prepare the MOF film layer by electrodeposition. It not only provides an electrolyte for anodization, but also provides a corrosion inhibitor for subsequent steps, reduces the discharge of acid waste liquid, and is more environmentally friendly. In addition, in the subsequent step of preparing MOF, the solution and the required corrosion inhibitor are mixed in one step, thereby simplifying the operation process. At the same time, the prepared MOF coated corrosion inhibitor film layer also has the function of corrosion resistance and self-repair, which further improves the corrosion resistance of the aluminum alloy surface. The purpose of the present invention is achieved through the following technical solutions:

[0005] The present invention provides a method for preparing a metal organic framework film layer with self-repairing performance by electrodeposition, which specifically comprises the following steps:

[0006] S1. Using an aluminum alloy as an anode and an aluminum foil as a cathode, oxidizing under pressure in a tannic acid solution to form an anodic oxide film on the surface of the aluminum alloy to obtain an anodic oxide aluminum alloy;

[0007] S2, adding N,N-dimethylformamide, metal source and trimesic acid to the tannic acid solution after the reaction and mixing them evenly to obtain a film preparation solution;

[0008] S3. Using anodized aluminum alloy as cathode and graphite as anode, electrodeposition is performed in the film preparation solution to form a self-repairing film on the aluminum alloy.

[0009] As some specific embodiments of the present invention, in step S1, the aluminum alloy is first subjected to grinding, degreasing and drying treatments in sequence before anodizing.

[0010] As some specific embodiments of the present invention, the degreasing liquid used in the degreasing treatment is a mixed solution of sodium silicate nonahydrate and sodium phosphate dodecahydrate.

[0011] Furthermore, in the degreasing liquid, the concentration of sodium silicate nonahydrate is 0.005-0.015 g / mL;

[0012] And / or, the concentration of the sodium phosphate dodecahydrate is 0.02-0.06 g / mL.

[0013] As some specific embodiments of the present invention, the oil removal treatment time is 1 to 3 min;

[0014] And / or, the temperature of the degreasing treatment is 70-80°C.

[0015] Preferably, the degreasing treatment time is 2 min;

[0016] And / or, the temperature of the degreasing treatment is 80°C.

[0017] As some specific embodiments of the present invention, after the degreasing treatment, the aluminum alloy is ultrasonically cleaned in ethanol and distilled water.

[0018] As some specific embodiments of the present invention, in step S1, the concentration of the tannic acid solution is 0.01-0.03 g / mL.

[0019] Preferably, in step S1, the concentration of the tannic acid solution is 0.01 g / mL. The present invention also optimizes the concentration of tannic acid as an anodic oxidation solution, because different concentrations will affect the film-forming effect of the anodic oxidation film on the metal surface, thereby affecting the subsequent electrodeposition preparation of the MOF film. After optimization, the optimal concentration of tannic acid is 10 g / L, i.e., 0.01 g / mL.

[0020] As some specific embodiments of the present invention, in step S1, the voltage of the pressurized oxidation is 10-20 V;

[0021] And / or, the pressurized oxidation time is 0.5 to 1.5 h.

[0022] As some specific embodiments of the present invention, in step S1, after obtaining the anodized aluminum alloy, it is cleaned and dried.

[0023] As some specific embodiments of the present invention, in step S2, when preparing the film preparation solution, the volume ratio of N,N-dimethylformamide to tannic acid solution added is 3:2~2:3;

[0024] And / or, in the film layer preparation solution, the concentration of trimesic acid is 0.015-0.035 g / mL.

[0025] As some specific embodiments of the present invention, in step S2, the metal source is at least one of cerium nitrate hexahydrate, cobalt nitrate hexahydrate, and nickel nitrate hexahydrate.

[0026] As some specific embodiments of the present invention, in step S2, the concentration of the metal source is 0.03-0.07 g / mL.

[0027] Preferably, the metal source is cerium nitrate hexahydrate, and the concentration of the cerium nitrate hexahydrate is 0.03-0.07 g / mL.

[0028] As some specific embodiments of the present invention, the self-healing film layer is metal-MOF@TA, specifically at least one of Ce-MOF@TA, Co-MOF@TA, and Ni-MOF@TA.

[0029] As some specific embodiments of the present invention, in step S3, the voltage of electrodeposition is 8 to 20 V;

[0030] and / or, the temperature of the electrodeposition is 20-30°C;

[0031] And / or, the electrodeposition time is 20 to 60 min.

[0032] Preferably, in step S3, the voltage of electrodeposition is 15 V;

[0033] and / or, the electrodeposition temperature is 25°C;

[0034] And / or, the electrodeposition time is 40 min.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The present invention uses tannic acid, a corrosion inhibitor of polyphenol weak acid, as the acid solution of the anodic oxidation solution, which can not only prepare an anodic oxidation film on the metal surface, but also continue to serve as a raw material for the subsequent preparation of a metal-MOF self-repairing film layer; thereby reducing the use of waste acid and simplifying the preparation process;

[0037] (2) The anodizing and electrodeposition steps of the present invention use low voltage and short time, which is more energy-saving and environmentally friendly;

[0038] (3) When preparing the film preparation liquid, the present invention adopts a method of adding and dissolving the raw materials in one step, which simplifies the preparation steps, and the prepared self-repairing film layer has excellent self-repairing properties;

[0039] (4) The electrochemical test of the self-repairing film showed that the corrosion current density could reach 3.65×10 -9 A.cm -2 The anti-corrosion efficiency of aluminum alloy reaches 99.97%, and the AC impedance value reaches 4.83×10 7 Ω·cm 2 , the electrochemical performance of the self-repairing film prepared by the present invention is better;

[0040] (5) The self-repairing film layer was immersed in 3.5 wt.% sodium chloride salt water and 5 wt.% sodium chloride neutral salt spray test. After immersion in salt water for 14 days, the film layer was still intact and had good corrosion resistance. In the neutral salt spray test, no obvious changes were found on the surface of the film layer after 80 days of salt spray, which showed good corrosion resistance and salt spray resistance.

[0041] (6) The EDS carbon and oxygen element spectrum analysis of the scratched part of the self-repairing film before and after salt spray was carried out. After the salt spray test, the content of C and O elements in the scratched part increased significantly compared with that before salt spray. The corrosion inhibitor tannic acid was released on the surface of the aluminum alloy and actively combined with aluminum ions to form an anti-corrosion metal complex, forming a layer of corrosion inhibition film, which provided secondary protection for the aluminum alloy and repaired the aluminum alloy surface at the scratched part, preventing the corrosive medium from contacting the substrate, thereby achieving the purpose of continuing to protect the metal surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0043] Figure 1 The SEM images of the aluminum alloy, the anodic oxide film and the Ce-MOF@TA film layer in Example 1; wherein a is a SEM image of the aluminum alloy, b is a SEM image of the porous oxide film (anodic oxide film) on the surface of the aluminum alloy, and c is a SEM image of the self-healing film layer Ce-MOF@TA formed on the surface of the aluminum alloy;

[0044] Figure 2 The electrochemical test results of the aluminum alloy, the anodized film and the Ce-MOF@TA film in Example 1, wherein a is the potentiodynamic polarization curve and b is the electrochemical impedance spectroscopy;

[0045] Figure 3 The electrochemical impedance modulus test spectrum of the aluminum alloy surface after the Ce-MOF@TA film layer is attached in Example 1 and then immersed in a 5 wt.% NaCl solution for 0-14 days;

[0046] Figure 4 This is a graph showing the results of a 0-80 day salt spray test after a film layer is attached to the surface of the aluminum alloy in Example 1;

[0047] Figure 5 EDS carbon and oxygen element spectra of the scratches before and after salt spray. a and b are the C and O elements of the scratches of Ce-MOF@TA before salt spray, respectively; c and d are the C and O elements of the scratches of Ce-MOP@TA after salt spray, respectively. DETAILED DESCRIPTION

[0048] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0049] Example 1

[0050] A method for preparing a corrosion-resistant Ce-MOF@TA self-repairing film layer coated with tannic acid is provided. The specific steps are:

[0051] (1) Aluminum alloy pretreatment

[0052] Aluminum alloy 6061 with a size of 15×15×3 mm was used as the substrate and polished with 180#, 600#, and 1000# sandpaper. A 50 mL aqueous solution of 0.5 g sodium silicate 9hydrate and 2 g sodium phosphate 12hydrate was prepared as the degreasing solution. The polished aluminum alloy sheet was placed in the degreasing solution and degreased at 80°C for 2 min, then ultrasonically cleaned with ethanol and distilled water for 10 min, and then taken out and dried for use.

[0053] (2) Preparation of anodized film:

[0054] Weigh 0.4 g of tannic acid to prepare 20 mL of anodizing solution for later use;

[0055] The pretreated aluminum sheet was used as the anode and the aluminum foil as the cathode. A DC power supply was used to react in the anodizing solution at 15V at room temperature for 1 h. The aluminum sheet was taken out and rinsed with deionized water. The anodized film was obtained by drying in an oven.

[0056] (3) Preparation of Ce-MOF@TA film:

[0057] 20 mL of N,N-dimethylformamide was added to the anodizing solution, 2 g of cerium nitrate hexahydrate and 1 g of trimesic acid were added to the solution, and the solution was dissolved by ultrasonic stirring to obtain a film preparation solution;

[0058] The aluminum alloy containing the anodic oxide film layer was connected to the cathode of the DC power supply, and the graphite was connected to the anode of the DC power supply, and placed in the film preparation solution to form a current path. The deposition voltage was set to 15 V and the constant voltage deposition was performed at a temperature of 25°C for 40 min. After the deposition was completed, it was rinsed with distilled water and placed in a 50°C oven for drying.

[0059] The tannic acid, sodium silicate nonahydrate, sodium phosphate dodecahydrate, cerium nitrate hexahydrate, trimesic acid and N,N-dimethylformamide are all of chemical purity or above.

[0060] The self-repairing film layer prepared in Example 1 was verified for various properties, as follows:

[0061] 1. SEM morphology characterization

[0062] The aluminum alloy in Example 1, the anodic (porous) oxide film formed on the surface of the aluminum alloy, and the Ce-MOF@TA self-healing film layer formed on the surface of the aluminum alloy were characterized by SEM images. Figure 1 As shown. Among them, a is the SEM image of aluminum alloy, b is the SEM image of the porous oxide film on the surface of aluminum alloy, and c is the SEM image of Ce-MOF@TA. Figure 1 It can be seen that the Ce-MOF@TA self-healing film layer was successfully synthesized, has good bonding with the aluminum alloy substrate, and is evenly distributed on the aluminum alloy surface.

[0063] 2. Corrosion resistance test and electrochemical impedance test

[0064] The corrosion resistance of the Ce-MOF@TA self-healing film prepared in Example 1 was tested using a CHI760 electrochemical workstation in a three-electrode system (calomel electrode as reference electrode, platinum electrode as auxiliary electrode, aluminum alloy / aluminum alloy with anodized film on the surface / aluminum alloy with Ce-MOF@TA self-healing film on the surface as working electrode, 3.5 wt.% sodium chloride solution as electrolyte). The potentiodynamic polarization curve was used to study the corrosion resistance of the aluminum alloy surface film. After the open circuit potential was stabilized, the test was performed at a scan rate of 10 mV / s. The frequency range of the impedance test was 10 5 Hz to 10 -2 Hz, and a 10 mV sinusoidal signal perturbation was swept through the open circuit potential. The measured potentiodynamic polarization curve and electrochemical impedance spectrum are shown in Figure 2 shown.

[0065] according to Figure 2 The potentiodynamic polarization curve in a shows that the corrosion potential of the Ce-MOF@TA film on the aluminum alloy surface prepared in Example 1 is -0.553 V, and the corrosion current density is 3.65×10 -9 A.cm -2 The corrosion potential of the anodic oxide film is -0.698 V, and the corrosion current density is 9.42×10 -7 A.cm -2 The corrosion potential of 6061 aluminum alloy substrate is -0.699 V, and the corrosion current density is 1.24×10 -5 A.cm -2 It can be seen that the corrosion potential of the Ce-MOF@TA film layer shifted positively, and the corrosion current density was reduced by 4 and 2 orders of magnitude compared with the anodic oxide film and aluminum alloy substrate, respectively.

[0066] according to Figure 2 b shows the electrochemical impedance spectrum. It can be seen that after the Ce-MOF@TA film is prepared on the aluminum alloy surface, its impedance fitting results show the R ct The value is 2.58×10 3 Ω·cm 2 Increased to 4.83×10 7 Ω·cm2 , significantly improving the corrosion resistance of aluminum alloy, and the anti-corrosion efficiency of aluminum alloy can reach 99.97%.

[0067] The corrosion current density of the Ce-MOF@LS film prepared in patent CN116815268A is 1.045×10 -8 A.cm -2 , AC impedance value 3.0×10 6 Ω·cm 2 In comparison, the self-repairing film layer prepared by the present invention has lower corrosion current density, higher AC impedance value, better electrochemical performance, and stronger corrosion resistance.

[0068] 3. Immersion test and intermittent salt spray test

[0069] The working environment includes immersion test and intermittent salt spray test.

[0070] (1) Immersion test: The Ce-MOF@TA film prepared in Example 1 was immersed in a 3.5 wt.% NaCl solution, and the impedance test was performed on the film at 0, 2, 7, and 14 days. The change in the corrosion resistance of the film was analyzed by the modulus diagram. The results are as follows: Figure 3 shown.

[0071] From the modulus diagram of the immersion experiment ( Figure 3 ) analysis: Ce-MOF@TA membrane layer was immersed in salt solution, and its |Z| 0.01 The Hz value increased from 1.0×10 7 Ω·cm 2 Gradually reduced to 1.8×10 5 Ω·cm 2 On the fourteenth day, it slightly increased, which was two orders of magnitude lower than the initial level, but still maintained at the fifth power, thus providing a relatively long-lasting protection for the substrate. After fourteen days of immersion, the Ce-MOF@TA film still had good anti-corrosion ability.

[0072] (2) Salt spray test:

[0073] The test was conducted with a 12-hour spray (5 wt.% NaCl solution) and a 12-hour rest period. After the rest period, photos were collected for analysis. The results are as follows: Figure 4 shown.

[0074] From the salt spray results ( Figure 4), the Ce-MOF@TA film had no obvious corrosion spots after 80 days, and the pitting of the Ce-MOF@TA scratch film appeared for about 20 days, and no corrosion spots appeared elsewhere afterwards. This shows that in a salt spray environment, the Ce-MOF@TA film can protect the aluminum alloy substrate for a longer time. The film layer was destroyed after blocking the invasion of the corrosive medium, and then the tannic acid in the film layer actively combined with aluminum ions to form an anti-corrosion metal complex, forming a second protective film layer, which repaired the aluminum alloy surface at the scratch. In summary, the addition of corrosion inhibitor TA improves the durability of the film layer.

[0075] (3) Perform EDS image test on the film scratches before and after the salt spray test (such as Figure 5 As shown), the C and O elements are intercepted. Figure 5 a and b are the C and O elements at the scratch of Ce-MOF@TA before salt spray, Figure 5 c and d are the C and O elements at the scratch of Ce-MOF@TA after salt spray, respectively. It can be seen that after the salt spray test, the C and O elements in the scratch part have increased significantly compared with those before the salt spray, which indicates that the corrosion inhibitor is successfully released on the surface of the aluminum alloy, which helps to actively form a corrosion inhibition film on the metal matrix, preventing the corrosive medium from contacting the matrix, thereby achieving the purpose of continuing to protect the metal surface.

[0076] Example 2

[0077] A method for preparing a corrosion-resistant Ni-MOF@TA self-healing film layer coated with tannic acid is provided. The other steps for preparing the self-healing film layer are the same as those in Example 1, except that in step (3), cerium nitrate hexahydrate is replaced with nickel nitrate hexahydrate, and the amount of nickel nitrate hexahydrate added is 1.5 g. Nickel nitrate hexahydrate is of chemical purity or higher.

[0078] After the Ni-MOF@TA film was prepared on the aluminum alloy surface, its corrosion current density was measured to be 1.48×10 -7 A.cm -2 The Ni-MOF@TA film layer prepared in Example 2 also has good self-healing properties. After the Ni-MOF on the metal surface is destroyed, the released TA will be adsorbed on the aluminum alloy, and through the metal heteroatom / π electron interaction, it will coordinate with the aluminum ions to form a self-assembled corrosion-resistant film, thereby automatically repairing the original corrosion-resistant film defects on the aluminum alloy surface.

[0079] Example 3

[0080] A method for preparing a corrosion-resistant Co-MOF@TA self-healing film layer coated with tannic acid is provided. The other steps for preparing the self-healing film layer are the same as those in Example 1, except that in step (3), cerium nitrate hexahydrate is replaced with cobalt nitrate hexahydrate, and the amount of cobalt nitrate hexahydrate added is 1.5 g. The cobalt nitrate hexahydrate is of chemical purity or higher.

[0081] After the Co-MOF@TA film was prepared on the aluminum alloy surface, the corrosion current density was 1.45×10 -7 A.cm -2 The Co-MOF@TA film layer prepared in Example 3 also has good self-healing properties. After the Co-MOF on the aluminum alloy surface is destroyed, the released TA molecules coordinate with the aluminum ions through the metal heteroatom / π electron interaction to form a self-assembled corrosion-resistant film, thereby automatically repairing the original corrosion-resistant film defects on the aluminum alloy surface.

[0082] In addition to the metal sources cerium nitrate hexahydrate, nickel nitrate hexahydrate and cobalt nitrate hexahydrate used in Examples 1-3, the present invention also uses other metal sources for verification. The results show that when the cerium element in cerium nitrate hexahydrate is replaced by other elements such as Mn and Zn, it is impossible to further form a self-repairing film layer on the surface of the aluminum alloy after the anodized film is synthesized. Only Ce, Ni and Co elements can form a self-repairing film layer on the surface of the aluminum alloy.

[0083] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a metal organic framework film layer with self-repairing properties by electrodeposition, characterized in that: The steps include: S1. Using an aluminum alloy as an anode and an aluminum foil as a cathode, oxidizing under pressure in a tannic acid solution to form an anodic oxide film on the surface of the aluminum alloy to obtain an anodic oxide aluminum alloy; S2, adding N,N-dimethylformamide, metal source and trimesic acid to the tannic acid solution after the reaction and mixing them evenly to obtain a film preparation solution; S3. Using anodized aluminum alloy as cathode and graphite as anode, electrodeposition is performed in the film preparation solution to form a self-repairing film on the aluminum alloy.

2. The method according to claim 1, characterized in that In step S2, the metal source is at least one of cerium nitrate hexahydrate, cobalt nitrate hexahydrate, and nickel nitrate hexahydrate.

3. The method according to claim 1, characterized in that In step S1, the concentration of the tannic acid solution is 0.01-0.03 g / mL.

4. The method according to claim 1, characterized in that In step S1, the voltage of the pressurized oxidation is 10-20V; And / or, the pressurized oxidation time is 0.5 to 1.5 h.

5. The method according to claim 1, characterized in that In step S2, when preparing the film preparation solution, the volume ratio of N,N-dimethylformamide to tannic acid solution added is 3:2~2:3; and / or, in the film preparation solution, the concentration of trimesic acid is 0.015-0.035 g / mL; And / or, in the film preparation solution, the concentration of the metal source is 0.03-0.07 g / mL.

6. The method according to claim 1, characterized in that In step S3, the voltage of electrodeposition is 8 to 20 V; and / or, the temperature of the electrodeposition is 20-30°C; And / or, the electrodeposition time is 20 to 60 min.

7. The method according to claim 1, characterized in that In step S1, the aluminum alloy is first subjected to grinding, degreasing and drying treatments in sequence before anodizing.

8. The method according to claim 7, characterized in that The degreasing liquid used in the degreasing treatment is a mixed solution of sodium silicate nonahydrate and sodium phosphate dodecahydrate.

9. The method according to claim 8, characterized in that In the degreasing liquid, the concentration of sodium silicate nonahydrate is 0.005-0.015 g / mL; And / or, the concentration of the sodium phosphate dodecahydrate is 0.02-0.06 g / mL.

10. The method according to claim 7, characterized in that The degreasing treatment time is 1 to 3 minutes; And / or, the temperature of the degreasing treatment is 70-80°C.

Citation Information

Patent Citations

  • Method for preparing Ce-MOF corrosion inhibitor intelligent composite film layer on surface of aluminum alloy

    CN116815268A

  • Preparation method for in-situ growth of zinc-organic coordination coating on zinc surface

    CN117071021A

  • Method for improving surface corrosion resistance of 7-series aluminum alloy anode oxide film

    CN118880411A

  • Mixed acid anodization

    US20220154361A1